Effect of Trastuzumab on Notch-1 Signaling Pathway in Breast Cancer SK-BR3 Cells - Han, Ming; Deng, Hua-yu; Jiang, Rong (Chinese Journal of Cancer Research; Vol 24, No 3 (September 01, 2012): Chinese Journal of Cancer Research, 2012)
Objective: To investigate the effects and mechanisms of trastuzumab on Notch-1 pathway in breast cancer cells, recognizing the significance of Notch-1 signaling pathway in trastuzumab resistance. Methods: Immunocytochemistry staining and Western blotting were employed to justify the expression of Notch-1 protein in HER2-overexpressing SK-BR3 cells and HER2-non-overexpressing breast cancer MDA-MB-231 cells. Western blotting and reverse transcription PCR (RT-PCR) were used to detect the activated Notch-1 and Notch-1 target gene HES-1 mRNA expression after SK-BR3 cells were treated with trastuzumab. Double immunofluorescence staining and co-immunoprecipitation were used to analyze the relationship of Notch-1 and HER2 proteins. Results: The level of Notch-1 nuclear localization and activated Notch-1 proteins in HER2-overexpressing cells were significantly lower than in HER2-non-overexpressing cells (P